Diversity of Macro Fungi in Bung Hatta Forest Park Collection Block, Padang City, West Sumatera - Ainul Mardiah; Dezi Handayani (Jurnal Serambi Biologi, 2022)
The collection block is one of the blocks located in the Bung Hatta Forest Park. The condition of the area of the collection block allows the fungus to grow well. Macro fungi play an important role in forest ecosystems and have the potential as food, medicine, and some are poisonous. Considering the many types of macro fungi whose number and species are not yet known, an inventory needs to be carried out. This study aims to determine the types of macro fungi found in the Bung Hatta Forest Park Collection Block, Padang City. This research is descriptive research. The sampling technique used is the direct survey method by exploring the Collection Block area. The fungi samples found were taken and then put into a sample bottle and continued with the making of a herbarium and then identified in the botanical laboratory of FMIPA UNP. Identification of macro fungi using the Collins Fungi Guide (Buczacki, 2012) and journals. The data is presented in the form of tables and figures. The results of the study found 28 species of macro fungi consisting of 2 divisions, 2 classes, 8 orders, 14 families and 19 genera. It was concluded that the most abundant types of macro fungi were dominated by the Basidiomycota division and the least by the Ascomycota division.